DAMPAK PENGGUNAAN AIR KELAPA TERHADAP PERTUMBUHAN TANAMAN KACANG TOLO - Seniman Buulolo (Universitas Nias Raya, 2023)
Tolo beans are one of the local beans that have the potential to be developed, where tolo beans have many benefits for the surrounding community which is one of the traditional activities attached to certain community habits that can be used at every wedding ceremony and also if someone dies. The population in this study were all seeds of the tolo bean plant that had been bred, while the sample in this study was some of the tolo bean plant that had been seeded. This study aims to determine the impact of using coconut water on the growth of tolo bean (vigna unguiculata) plants. This type of research is a descriptive type of qualitative research. Based on the results of the research and discussion obtained, there are several conclusions that can be drawn in this study as follows: (1) Good cultivation of tolo bean plants can obtain good productivity results (2) Cultural preservation (local wisdom) through tolo beans which will be used as as babae is to use coconut water as a natural organic fertilizer that can have an effect or impact on plant growth, one of which is the tolo bean plant. . The suggestion in the research is that farmers should continue to preserve the planting of tolo beans which can be used as local wisdom and customs and utilize coconut water as a natural organic fertilizer that can have an impact on plant growth, one of which is the tolo bean plant.